Association of Butyryl Cholinesterase and Recurrent Ischemic Stroke: A Cross-Sectional Study - Chen R; Zhang K; Liu H; Liu L; Li H; Yan Y; Zhou Z; Meng C; Wang X; Wu H; Miao R; Wang R; et al. (International Journal of General Medicine)
Ruomeng Chen,1,2 Kun Zhang,1,2 Hui Liu,1,2 Lijuan Liu,1,2 Hui Li,3 Yan Yan,1,2 Zhou Zhou,1,2 Chaoyue Meng,1,2 Xuelin Wang,4 Haoran Wu,4 Ruihan Miao,4 Rui Wang,1,2 Xiaoyun Liu1,2,4,5 1Department of Neurology, The First Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Neurology, Hebei Hospital of Xuanwu Hospital Capital Medical University, Shijiazhuang, Hebei, People’s Republic of China; 3Department of Neurology, Hengshui People’s Hospital, Hengshui, Hebei, People’s Republic of China; 4Department of Neurology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 5Neuroscience Research Center, Medicine and Health Institute, Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Xiaoyun Liu, Department of Neurology, The First Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China, Email 57404217@hebmu.edu.cnObjective: Exploring novel relevant factors associated with recurrent ischemic stroke.Methods: This is a retrospective study, patients were divided into first-ever ischemic stroke group and recurrent ischemic stroke groups. We conducted a comparative analysis of baseline data between the two groups. Multifactorial logistic regression analysis was performed to identify factors associated with recurrent ischemic stroke. Grouped according to butyryl cholinesterase levels, to elucidate the relationship between butyryl cholinesterase levels and stroke recurrence.Results: A total of 2029 patients were included, with 1174 in the first-ever ischemic stroke group and 855 in the recurrent ischemic stroke group. Age, hypertension, diabetes, alanine aminotransferase, and lipoprotein(a) were identified as risk factors for recurrent ischemic stroke (ALL p< 0.05). Erythrocyte count, butyryl cholinesterase, low-density lipoprotein, and non-atherosclerotic type of large arteries were found to be negative associated with recurrent ischemic stroke (ALL p< 0.05). Subgroup analyses indicated that butyryl cholinesterase levels were significantly negatively associated with recurrent ischemic stroke in males (OR=0.814, p< 0.001, 95% CI: 0.761 ~ 0.871), especially under 60 years (OR=0.781, p< 0.001, 95% CI: 0.708 ~ 0.862). After adjusting for multifactorial regression analyses, the recurrent rate in the lowest quartile of butyryl cholinesterase levels was 2.281 times that of the highest quartile (OR=2.281, p< 0.05, 95% CI: 1.318 ~ 3.948).Conclusion: Age, hypertension, diabetes, alanine aminotransferase, and lipoprotein(a) are independent risk factors for the recurrence of ischemic stroke. The inverse association between butyryl cholinesterase levels and stroke recurrence suggests butyryl cholinesterase may serve as a potential target for therapeutic intervention to improve the prognosis of ischemic stroke.Keywords: recurrent ischemic stroke, butyryl cholinesterase, cross-sectional study, Lipoprotein a, cerebral infarction